Art, Money, and the Gift: J.S.G. Boggs’ (Im)possible Currency - Hoeller, Hildegard (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2010)
This essay examines money artist J.S.G.Boggs’ work in light of gift theories by Lewis Hyde and Jacques Derrida. Reconnecting the spheres of the gift and the market, Boggs’ art explodes Hyde’s binaries and creates a solution for the dilemma of the artist in a market-driven society. Boggs’ “money” transactions also show that his money art can make possible the (im)possible gift, in Derrida’s terms, through the trappings of market-exchange. Finally, Boggs’ art, through imitation and difference, exposes the absurdities of money exchange.